Determination of Halogens by Ion Chromatography in Edible Mushrooms after Microwave-Induced Combustion for Sample Preparation - Gilberto Silva Coelho Junior; Filipe Soares Rondan; Carla Andrade Hartwig; Rafael Francisco Santos; Paola Azevedo Mello; Marcia Foster Mesko (Journal of Analytical Methods in Chemistry)
In this study, the microwave-induced combustion (MIC) method was evaluated for the sample preparation of the most consumed mushroom species in Brazil (Champignon, Shiitake, and Shimeji) and further halogen determination by ion chromatography (IC). For this, sample mass, combustion aid mass, and absorbing solution (H2O and 50 mmol·L−1, 100 mmol·L−1, or 150 mmol·L−1 NH4OH) were evaluated. Bromine and iodine concentrations, determined by IC, were lower than the limits of detection (LODs, Br: 6 mg·kg−1 and I: 24 mg·kg−1). Inductively coupled plasma mass spectrometry (ICP-MS) was also used for Br and I determination, and the LODs were lower (Br: 0.066 mg·kg−1 and I: 0.014 mg·kg−1) than those obtained by IC. Concentrations of Cl, obtained by IC, ranged from 523 mg·kg−1 to 13053 mg·kg−1 with LOD of 40 mg·kg−1. In turn, Br and I concentrations, obtained by ICP-MS, ranged from 2.49 mg·kg−1 to 5.50 mg·kg−1 and from <0.014 mg·kg−1 to 0.047 mg·kg−1, respectively. Fluorine concentrations, determined by IC, were always lower than LOD (23 mg·kg−1). The trueness of the proposed methods was evaluated by recovery tests using standard solutions and a reference material (RM NIST 8435). When using the standard solution, recoveries ranged from 95% to 103% for halogen determination by IC and from 105% to 109% for Br and I determination by ICP-MS. When using the RM, recoveries of 102% for Cl by IC and of 87% and 86% for Br and I by ICP-MS, respectively, were obtained.